Insulating impregnating varnish and preparation method thereof

Unsaturated polyester resin is prepared by using castor oil modified polyester polyol and adding boron nitride nanosheet composite sol, the problem of insufficient thermal conductivity of impregnated paint is solved. The resulting in insulated impregnated paint has high thermal conductivity and heat resistance. , improves the motor's heat dissipation ability and service life.

CN119463651AInactive Publication Date: 2025-02-18HUIZHOU JUXIN CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411461269.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The impregnated paint at this stage cannot meet the lower viscosity and high thermal conductivity at the same time, which affects the motor's heat dissipation ability and service life.

Method used

Unsaturated polyester resin is prepared by using castor oil modified polyester polyol, and a composite sol of boron nitride nanosheet doped with silicon particles is added to the paint system to improve the thermal conductivity of the paint.

Benefits of technology

The resulting insulating impregnated paint has the characteristics of high thermal conductivity, high heat resistance and low viscosity, which improves the heat dissipation ability and service life of the motor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091933700000041
    Figure BDA0005091933700000041
  • Figure BDA0005091933700000071
    Figure BDA0005091933700000071
Patent Text Reader

Abstract

The invention belongs to the technical field of insulating materials, and discloses insulating impregnating varnish and a preparation method thereof. The insulating impregnating varnish is prepared from the following raw materials: unsaturated polyester resin, epoxy resin, a curing agent, a diluent, an initiator, a polymerization inhibitor and composite sol, wherein the unsaturated polyester resin is prepared from castor oil modified polyester polyol, and the composite sol is prepared from tetraethyl orthosilicate and boron nitride nanosheets. Under the combined action of the unsaturated polyester resin prepared from the specific polyol and the composite sol, the prepared insulating impregnating varnish has the characteristics of high thermal conductivity, high heat resistance and low viscosity, has excellent mechanical properties and electrical properties, can improve the heat dissipation capability of the motor in the use process when being applied to the motor, and can improve the service life of the motor. And the service life of the motor is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of insulating materials, and in particular to an insulating impregnating varnish and a preparation method thereof. Background Art

[0002] In the manufacturing process of high-speed rail traction motors, electric tools, new energy vehicle motors, etc., high-heat-resistant impregnation varnish is needed as stator winding fixation bonding and supplementary insulation. Due to the particularity of the motor manufacturing process, the paint liquid is required to have low viscosity and high storage stability to facilitate impregnation construction. At the same time, the impregnation varnish is also required to have advantages such as high insulation, heat resistance, mechanical strength and resistance to cold and hot shock after curing. At this stage, the mainstream impregnation varnish products are silicone-based. Although they have excellent heat resistance, problems such as low high-temperature mechanical strength and easy cracking still affect the service life of heat-resistant motors. At the same time, the insulating material with low thermal conductivity hinders the heat exchange between the stator winding and the rotor winding to a certain extent, resulting in the aging of the insulating materials of the stator winding and the rotor winding, shortening the life of the motor. Therefore, it is of great significance to develop an insulating impregnation varnish that improves its thermal conductivity without affecting the mechanical and heat-resistant properties of the motor, which is of great significance for the structural optimization and performance improvement of high-speed motors. Summary of the invention

[0003] In order to solve the above technical problems, an insulating impregnating varnish with high thermal conductivity and high heat resistance is developed, thereby reducing the temperature rise rate of the motor during use. The present application provides an insulating impregnating varnish and a preparation method.

[0004] In the first aspect, the present application provides an insulating impregnating varnish comprising the following raw materials in parts by weight: 45-80 parts of unsaturated polyester resin, 30-60 parts of epoxy resin, 4-6 parts of curing agent, 10-25 parts of diluent, 0.5-1 part of initiator, 0.1-0.25 part of inhibitor, and 3-7 parts of composite sol; the raw materials of the unsaturated polyester resin include a first polyol, a second polyol and a polyacid; the first polyol is a castor oil-modified polyester polyol; the raw materials of the composite sol include tetraethyl orthosilicate and boron nitride nanosheets.

[0005] By adopting the above technical scheme, the castor oil-modified polyester polyol used to make unsaturated polyester resin has the characteristics of low viscosity, aging resistance, high ignition point, good stability, etc., so that the prepared unsaturated polyester resin has good high temperature resistance and low viscosity characteristics. In addition, the present application compounded the composite sol with unsaturated polyester resin and epoxy resin, and the composite sol was doped with boron nitride nanosheets containing silicon particles. The dual effects of silicon particles and boron nitride nanosheets make the insulating impregnating varnish have excellent thermal conductivity. When used in motors, it can improve the heat dissipation capacity of the motor during use, reduce the temperature rise of the motor during use, and improve the power and life of the motor.

[0006] Optionally, the raw materials of the unsaturated polyester resin include a first polyol, a second polyol and a polyacid in a weight ratio of 8-15:12-26:20-35.

[0007] Optionally, the preparation method of the castor oil modified polyester polyol comprises the following steps: mixing castor oil and diethylene glycol, adding titanate, heating to 180-200°C, reacting for 2-3h, cooling to 130-150°C, adding succinic acid, heating to 180-200°C, reacting for 4-6h, cooling to room temperature, adding triethylamine, mixing and reacting for 20-30min, and obtaining castor oil modified polyester polyol.

[0008] Preferably, the preparation method of castor oil modified polyester polyol comprises the following steps: mixing castor oil with diethylene glycol, adding titanate under argon atmosphere, heating to 185°C, reacting for 2.4 hours, cooling to 135°C, adding succinic acid, heating to 185°C, reacting for 4 hours, cooling to room temperature, adding triethylamine, mixing and reacting for 30 minutes, and obtaining castor oil modified polyester polyol. The weight ratio of castor oil, diethylene glycol, titanate, succinic acid and triethylamine is 40:10:0.8:2.5:0.2.

[0009] Optionally, the second polyol includes one or more of ethylene glycol, propylene glycol, butanediol, and neopentyl glycol; the polyacid includes one or more of isophthalic acid, terephthalic acid, glutaric acid, adipic acid, sebacic acid, phthalic anhydride, maleic anhydride, methyltetrahydrophthalic anhydride, and maleic acid.

[0010] Optionally, the epoxy resin includes one or more of bisphenol A epoxy resin E20, epoxy resin E44, and epoxy resin E51.

[0011] Optionally, the preparation process of the composite sol includes the following steps: adding tetraethyl orthosilicate and water into a reaction container, adjusting the pH, stirring at 40°C until the liquid is clear and transparent, adding boron nitride nanosheets, ultrasonically dispersing at 60°C, cooling, and standing to obtain a composite sol.

[0012] Preferably, the preparation process of the composite sol comprises the following steps: adding tetraethyl orthosilicate and water into a reaction container, adjusting the pH to 2-3, stirring at 40°C until the liquid becomes clear and transparent, adding boron nitride nanosheets, ultrasonically dispersing at 60°C for 15 minutes, cooling to 25°C, and standing for 2 hours to obtain a composite sol; wherein the weight ratio of tetraethyl orthosilicate, water and boron nitride nanosheets is 5:10:0.3.

[0013] Optionally, the boron nitride nanosheets are modified boron nitride nanosheets, and the preparation method of the modified boron nitride nanosheets comprises the following steps: adding the boron nitride nanosheets to water, sonicating at 30-80°C, adding a surface modifier, sonicating, adding a coupling agent, sonicating, filtering, and drying to obtain modified boron nitride nanosheets.

[0014] Preferably, the boron nitride nanosheet is a modified boron nitride nanosheet, and the preparation method of the modified boron nitride nanosheet comprises the following steps: adding the boron nitride nanosheet to water, the mass fraction of the boron nitride nanosheet is 10%, ultrasonicating at 60°C for 10 minutes, adding a surface modifier, ultrasonicating for 15 minutes, adding a coupling agent, ultrasonicating for 15 minutes, filtering, and drying to obtain the modified boron nitride nanosheet. The weight ratio of the boron nitride nanosheet, the surface modifier, and the coupling agent is 1:0.05:0.03.

[0015] Optionally, the surface modifier includes one or more of hexadecyl quaternary ammonium salt and octadecyl quaternary ammonium salt.

[0016] In a second aspect, the present application provides a method for preparing the above-mentioned insulating impregnating varnish, comprising the following steps: The first polyol, the second polyol and the polyacid are mixed in a reaction container, and the temperature is raised to 160-200°C for reaction. When the acid value is reduced to 35-50 mgKOH / g, vacuum is applied until the acid value is reduced to 20-25 mgKOH / g to obtain an unsaturated polyester resin. The temperature is lowered, and epoxy resin and composite sol are added to react for 0.5-1h. An inhibitor is added and mixed. A diluent is added and mixed. An initiator and a curing agent are added and mixed to obtain an insulating impregnation varnish.

[0017] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The insulating impregnating varnish prepared in the present application has the characteristics of high thermal conductivity, high heat resistance and low viscosity, and has excellent mechanical and electrical properties. When used in motors, it can improve the heat dissipation capacity of the motor during use, and increase the power and life of the motor. DETAILED DESCRIPTION

[0018] The present application designs an insulating impregnating varnish, comprising the following raw materials in parts by weight: 45-80 parts of unsaturated polyester resin, 30-60 parts of epoxy resin, 4-6 parts of curing agent, 10-25 parts of diluent, 0.5-1 part of initiator, 0.1-0.25 part of inhibitor, and 3-7 parts of composite sol; the raw materials of the unsaturated polyester resin include a first polyol, a second polyol and a polyacid; the first polyol is a castor oil-modified polyester polyol; the raw materials of the composite sol include tetraethyl orthosilicate and boron nitride nanosheets.

[0019] The raw materials of the unsaturated polyester resin include a first polyol, a second polyol and a polyacid in a weight ratio of 8-15:12-26:20-35.

[0020] The preparation method of the castor oil modified polyester polyol comprises the following steps: mixing castor oil and diethylene glycol, adding titanate, heating to 180-200° C., reacting for 2-3 hours, cooling to 130-150° C., adding succinic acid, heating to 180-200° C., reacting for 4-6 hours, cooling to room temperature, adding triethylamine, mixing and reacting for 20-30 minutes, and preparing the castor oil modified polyester polyol.

[0021] The preparation process of the composite sol comprises the following steps: adding tetraethyl orthosilicate and water into a reaction container, adjusting pH, stirring at 40°C until the liquid becomes clear and transparent, adding boron nitride nanosheets, ultrasonically dispersing at 60°C, cooling, and standing to obtain the composite sol.

[0022] The insulating impregnating varnish of the present application is prepared by the following method, comprising the following steps: The first polyol, the second polyol and the polyacid are mixed in a reaction container, and the temperature is raised to 160-200°C for reaction. When the acid value is reduced to 35-50 mgKOH / g, vacuum is applied until the acid value is reduced to 20-25 mgKOH / g to obtain an unsaturated polyester resin. The temperature is lowered, and epoxy resin and composite sol are added to react for 0.5-1h. An inhibitor is added and mixed. A diluent is added and mixed. An initiator and a curing agent are added and mixed to obtain an insulating impregnation varnish.

[0023] The technical problem solved by this application is that the current impregnation varnish products cannot simultaneously meet the requirements of low viscosity and high thermal conductivity. The development of an insulating impregnation varnish that improves the thermal conductivity of the motor without affecting its mechanical and heat-resistant properties is of great significance for the structural optimization and performance improvement of high-speed motors. This application prepares unsaturated polyester resin using castor oil-modified polyester polyol as raw material, and at the same time adds boron nitride nanosheet composite sol doped with silicon particles to the paint system to comprehensively improve its thermal conductivity and thermal conductivity. The obtained insulating impregnation varnish has the characteristics of high thermal conductivity, high heat resistance and low viscosity, and has excellent mechanical and electrical properties. It can be used in motors to improve the heat dissipation capacity of the motor during use and improve the power and life of the motor.

[0024] The present application is further described in detail below in conjunction with specific embodiments.

[0025] Examples 1-5 Examples 1-5 are insulating impregnating varnishes made with different raw material ratios, the difference being that the raw material ratios and amounts are different, as shown in Table 1 (unit: parts by weight).

[0026] Table 1 The epoxy resin used in Examples 1-5 is bisphenol A epoxy resin, model E20.

[0027] The curing agent used in Examples 1-5 is zinc octoate (CAS: 136-53-8).

[0028] The diluent used in Examples 1-5 was neopentyl glycol diacrylate (CAS: 2223-82-7).

[0029] The initiator used in Examples 1-5 was dicumyl peroxide (CAS: 80-43-3).

[0030] The polymerization inhibitor used in Examples 1-5 was methyl hydroquinone (CAS: 150-76-5).

[0031] The preparation process of the composite sol in Examples 1-5 comprises the following steps: Tetraethyl orthosilicate and water are added to a reaction container, the pH is adjusted to 2-3, and the mixture is stirred at 40°C until the liquid becomes clear and transparent. Boron nitride nanosheets are added, and the mixture is ultrasonically dispersed at 60°C for 15 minutes. The mixture is cooled to 25°C and allowed to stand for 2 hours to obtain a composite sol. The weight ratio of tetraethyl orthosilicate, water and boron nitride nanosheets is 5:10:0.3.

[0032] The raw materials of the unsaturated polyester resin in Examples 1-5 are the first polyol, the second polyol and the polyacid in a weight ratio of 10:20:25. Among them, the first polyol is castor oil modified polyester polyol, the second polyol is neopentyl glycol, and the polyacid is methyltetrahydrophthalic anhydride. The preparation method of castor oil modified polyester polyol comprises the following steps: Castor oil and diethylene glycol were mixed, titanate was added under argon atmosphere, the temperature was raised to 185°C, the reaction was continued for 2.4 hours, the temperature was lowered to 135°C, succinic acid was added, the temperature was raised to 185°C, the reaction was continued for 4 hours, the temperature was lowered to room temperature, triethylamine was added, the mixture was mixed and reacted for 30 minutes, and castor oil modified polyester polyol was obtained. The weight ratio of castor oil, diethylene glycol, titanate, succinic acid and triethylamine was 40:10:0.8:2.5:0.2.

[0033] The preparation process of Examples 1-5 comprises the following steps: The first polyol, the second polyol and the polyacid are mixed in a reaction container, and the temperature is raised to 180°C for reaction. When the acid value is reduced to 35 mgKOH / g, vacuum is applied until the acid value is reduced to 25 mgKOH / g to obtain an unsaturated polyester resin. The temperature is lowered to 150°C, and epoxy resin and composite sol are added, and the reaction is carried out for 0.5 h. An inhibitor is added, and the mixture is mixed. When the temperature is naturally cooled to 75°C, a diluent is added, and the mixture is mixed. When the temperature is naturally cooled to 50°C, an initiator and a curing agent are added, and the mixture is mixed. The mixture is allowed to stand for 5 h to obtain an insulating impregnating varnish.

[0034] Example 6 Example 6 is based on Example 2, with the difference that the second polyol used to prepare the unsaturated polyester resin in Example 6 is a mixture of propylene glycol and butanediol in a weight ratio of 1:1.

[0035] Example 7 Example 7 is based on Example 2, except that the polyacid used in preparing the unsaturated polyester resin in Example 7 is a mixture of terephthalic acid and maleic acid in a weight ratio of 1:1.

[0036] Embodiment 8-9 Example 8 is based on Example 2, except that the weight ratio of the first polyol, the second polyol and the polyacid used to prepare the unsaturated polyester resin in Example 8 is changed to 8:26:20.

[0037] Example 9 is based on Example 2, except that the weight ratio of the first polyol, the second polyol and the polyacid used to prepare the unsaturated polyester resin in Example 9 is changed to 15:12:35.

[0038] Example 10 Example 10 is based on Example 2, except that the epoxy resin used in Example 10 is bisphenol A epoxy resin model E51 by weight.

[0039] Embodiment 11 Example 11 is based on Example 2, except that: the boron nitride nanosheets used in preparing the composite sol in Example 11 are modified boron nitride nanosheets, and the preparation method of the modified boron nitride nanosheets comprises the following steps: adding boron nitride nanosheets to water, controlling the mass fraction of the boron nitride nanosheets to be 10%, ultrasonicating at 60°C for 10 minutes, adding a surface modifier octadecyl quaternary ammonium salt, ultrasonicating for 15 minutes, adding a coupling agent TMC-201, ultrasonicating for 15 minutes, filtering, and drying to obtain modified boron nitride nanosheets. Wherein, the weight ratio of the boron nitride nanosheets, the surface modifier, and the coupling agent is 1:0.05:0.03.

[0040] Accordingly, the preparation process of the composite sol in Example 11 comprises the following steps: Tetraethyl orthosilicate and water are added to a reaction container, the pH is adjusted to 2-3, and the mixture is stirred at 40°C until the liquid becomes clear and transparent. Modified boron nitride nanosheets are added, and ultrasonic dispersion is performed at 60°C for 15 minutes. The mixture is cooled to 25°C and allowed to stand for 2 hours to obtain a composite sol. The weight ratio of tetraethyl orthosilicate, water and modified boron nitride nanosheets is 5:10:0.3.

[0041] Comparative Example 1 Comparative Example 1 is based on Example 2, except that: the first polyol used to prepare the unsaturated polyester resin in Comparative Example 1 is replaced by propylene glycol in an equal amount, that is, the raw materials of the unsaturated polyester resin in Comparative Example 1 are propylene glycol, neopentyl glycol and methyltetrahydrophthalic anhydride in a weight ratio of 10:20:25.

[0042] Comparative Example 2 Comparative Example 2 is based on Example 2, except that: the first polyol is not used in preparing the unsaturated polyester resin in Comparative Example 2, that is, the raw materials of the unsaturated polyester resin in Comparative Example 2 are neopentyl glycol and methyltetrahydrophthalic anhydride in a weight ratio of 20:25.

[0043] Comparative Example 3 Comparative Example 3 is based on Example 2, except that the boron nitride nanosheets are replaced with nano-aluminum oxide in Comparative Example 3. Accordingly, the preparation process of the composite sol in Comparative Example 3 includes the following steps: Tetraethyl orthosilicate and water were added to a reaction container, the pH was adjusted to 2-3, and the mixture was stirred at 40°C until the liquid became clear and transparent. Nano-alumina was added, and the mixture was ultrasonically dispersed at 60°C for 15 minutes. The mixture was cooled to 25°C and allowed to stand for 2 hours to obtain a composite sol. The weight ratio of tetraethyl orthosilicate, water and nano-alumina was 5:10:0.3.

[0044] Performance testing: 1. The viscosity (mPa·s) of the insulating impregnating varnishes prepared in Examples 1-11 and Comparative Examples 1-3 at 23° C. was measured with reference to Standard GB / T 10247-2008.

[0045] 2. The thermal conductivity (mk) of the insulating impregnating varnishes prepared in Examples 1-11 and Comparative Examples 1-3 was determined with reference to Standard GB / T 11205-2009.

[0046] 3. The heat resistance grade (°C) of the insulating impregnating varnishes prepared in Examples 1-11 and Comparative Examples 1-3 was determined with reference to Standard GB / T 11026-2016.

[0047] 4. The tensile strength (MPa) of the insulating impregnating varnishes prepared in Examples 1-11 and Comparative Examples 1-3 was determined with reference to Standard GB / T 1040-2018.

[0048] 5. The breakdown field strength (MV / m) of the insulating impregnating varnishes prepared in Examples 1-11 and Comparative Examples 1-3 was determined with reference to Standard GB / T 1408.3-2016.

[0049] 6. The volume resistivity (Ω·m) of the insulating impregnating varnishes prepared in Examples 1-11 and Comparative Examples 1-3 was determined with reference to Standard GB / T 20160-2006.

[0050] The measurement results are shown in Table 2.

[0051] Table 2 By analyzing the data in Table 2 and comparing the performance data of Examples 1-11 with those of Comparative Examples 1-3, it can be seen that the insulating impregnating varnish prepared in the present application has the characteristics of high thermal conductivity, high heat resistance and low viscosity, and has excellent mechanical properties and electrical properties. In particular, by comparing Example 2 with Comparative Examples 1-3, it can be seen that the castor oil-modified polyester polyol used to prepare the unsaturated polyester resin and the boron nitride nanosheets used to prepare the composite sol have a significant effect on the high thermal conductivity, high heat resistance and low viscosity of the insulating impregnating varnish prepared in the present application.

[0052] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An insulating impregnating varnish, characterized in that: The method comprises the following raw materials in parts by weight: 45-80 parts of unsaturated polyester resin, 30-60 parts of epoxy resin, 4-6 parts of curing agent, 10-25 parts of diluent, 0.5-1 parts of initiator, 0.1-0.25 parts of inhibitor, and 3-7 parts of composite sol; The raw materials of the unsaturated polyester resin include a first polyol, a second polyol and a polyacid; The first polyol is castor oil modified polyester polyol; The raw materials of the composite sol include tetraethyl orthosilicate and boron nitride nanosheets.

2. The insulating impregnating varnish according to claim 1, characterized in that: The raw materials of the unsaturated polyester resin include a first polyol, a second polyol and a polyacid in a weight ratio of 8-15:12-26:20-35.

3. The insulating impregnating varnish according to claim 1, characterized in that: The preparation method of the castor oil modified polyester polyol comprises the following steps: mixing castor oil and diethylene glycol, adding titanate, heating to 180-200° C., reacting for 2-3 hours, cooling to 130-150° C., adding succinic acid, heating to 180-200° C., reacting for 4-6 hours, cooling to room temperature, adding triethylamine, mixing and reacting for 20-30 minutes, and preparing the castor oil modified polyester polyol.

4. The insulating impregnating varnish according to claim 1, characterized in that: The second polyol includes one or more of ethylene glycol, propylene glycol, butanediol, and neopentyl glycol; the polyacid includes one or more of isophthalic acid, terephthalic acid, glutaric acid, adipic acid, sebacic acid, phthalic anhydride, maleic anhydride, methyltetrahydrophthalic anhydride, and maleic acid.

5. The insulating impregnating varnish according to claim 1, characterized in that: The epoxy resin includes one or more of bisphenol A epoxy resin E20, epoxy resin E44, and epoxy resin E51.

6. The insulating impregnating varnish according to claim 1, characterized in that: The insulating impregnating varnish according to claim 1 is characterized in that the preparation process of the composite sol comprises the following steps: adding tetraethyl orthosilicate and water into a reaction container, adjusting the pH, stirring at 40°C until the liquid is clear and transparent, adding boron nitride nanosheets, ultrasonically dispersing at 60°C, cooling, and standing to obtain a composite sol.

7. The insulating impregnating varnish according to claim 6, characterized in that: The boron nitride nanosheet is a modified boron nitride nanosheet. The preparation method of the modified boron nitride nanosheet comprises the following steps: adding the boron nitride nanosheet into water, ultrasonicating at 30-80°C, adding a surface modifier, ultrasonicating, adding a coupling agent, ultrasonicating, filtering, and drying to obtain the modified boron nitride nanosheet.

8. The insulating impregnating varnish according to claim 7, characterized in that: The surface modifier includes one or more of hexadecyl quaternary ammonium salt and octadecyl quaternary ammonium salt.

9. A method for preparing the insulating impregnating varnish according to any one of claims 1 to 8, characterized in that: The following steps are involved: The first polyol, the second polyol and the polyacid are mixed in a reaction container, and the temperature is raised to 160-200°C for reaction. When the acid value is reduced to 35-50 mgKOH / g, vacuum is applied until the acid value is reduced to 20-25 mgKOH / g to obtain an unsaturated polyester resin. The temperature is lowered, and epoxy resin and composite sol are added to react for 0.5-1h. An inhibitor is added and mixed. A diluent is added and mixed. An initiator and a curing agent are added and mixed to obtain an insulating impregnation varnish.

Citation Information

Patent Citations

  • Insulating paint for variable frequency motor and preparation method thereof

    CN101892006A

  • Heat-conducting silicone rubber prepared by coating boron nitride with silicon dioxide as well as preparation method and application of heat-conducting silicone rubber

    CN109880372A

  • Polyurethane heat-conducting structural adhesive and preparation method thereof

    CN118064102A